Affirmative Actionrole And Participation Of Women 30% Representation In Political Parties And Parliament - Dinda Suciana Rambe (ISNU Nine-Star Multidisciplinary Journal, 2024)
This study examines the role of affirmative action in promoting women's participation through the 30% representation quota in political parties and parliament. Women's involvement in politics remains limited, and the quota system is a key policy tool to enhance gender equality in political decision-making. However, achieving meaningful representation requires more than just policy mandates; it demands strategic efforts to empower women within political structures. The research uses a juridical-normative approach, focusing on the legal framework governing affirmative action and the 30% quota for women in politics. Primary legal sources, including national laws and international conventions, are analyzed alongside secondary data from academic literature and case studies. The analysis evaluates the effectiveness of the quota system in enhancing women's roles in political parties and parliament and identifies factors that facilitate or hinder progress toward gender parity. The findings reveal that while the 30% quota policy has opened the door for greater female participation, its success depends on several factors. These include political party commitment to gender equality, the effectiveness of recruitment processes, and the provision of political education and mentorship for women. Furthermore, issues such as internal party culture, societal attitudes toward women in leadership, and the lack of comprehensive implementation strategies remain significant obstacles. The research also highlights the importance of political education, open recruitment systems, and women supporting each other to ensure sustainable progress. In conclusion, while the affirmative action policy and quota system are important steps toward achieving gender equality in politics, more targeted efforts are required. These include advancing women's political skills, ensuring open recruitment processes, and institutionalizing women's issues within party agendas. Political parties must take a proactive role in supporting female candidates and leaders to fulfill the long-term goals of gender parity.